Software Development in Disruptive Times: Creating a software solution with fast decision capability, agile project management, and extreme low-code technology. - VARAJÃO, JOÃO (Communications of the ACM, 2021)
The article describes a software-development project amid disruptions. It discusses the plan and execution of the Health Vigilance and Control Software product from the software firm Quidgest amid the COVID-19 pandemic that began in mid-March 2020. It examines development requirements, project management, and development technology, in addition to the use of low-code technology.